ANALYSIS OF LABOUR PRODUCTIVITY IN THE WORK OF LIGHT STEEL ROOF FRAME STRUCTURE (CASE STUDY: CONSTRUCTION PROJECT OF THE CATHOLIC CHURCH OF St. MARIA BUNDA PENGHARAPAN BUNUT SANGGAU) - Surya, Elisabet Katharin; Lusiana, Lusiana; Nuh, Saffarudin M. (Jurnal Teknik Sipil, 2024)
Project performance is greatly influenced by labor productivity. The productivity of each worker is different and is influenced by several factors such as work experience, age, education level, wages, site conditions, weather, coordination and planning, and leadership skills. This study examines the value and level of labor productivity, the variables that influence productivity, and the efforts to improve labor productivity. Observations in this study were conducted using the construction sampling method to observe the work scope, construction time, number of workers, adequate time, contribution time, ineffective time of lightweight steel-roof frame construction work, and direct on-site observation. Next, the level of labor productivity must be analyzed using the Labor Utilization Rate (LUR) approach. The analysis shows that the average productivity values for horse labor were 2,581 m ²/OH for ironworkers and 5,197 m ²/OH for manual workers. The productivity value for ironworkers in lath construction is 5,256 m ²/OH. From the analysis of the average level of labor productivity (results are more than 50% of her), it can be concluded that the level of labor productivity in the construction project of the catholic church of St. Maria Bunda Pengharapan Bunut Sanggau is satisfactory. The most significant variables affecting labor productivity are control variables. As a result of interviews with stakeholders, it was found that ways to increase labor productivity include effectively using time, creating a working system that is easy to work in, ensuring that workers have specialized knowledge, and ensuring thorough on-site supervision. Improvements are needed to create a good working environment.